2020
DOI: 10.5194/bg-2020-49
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reviews and syntheses: The mechanisms underlying carbon storage in soil

Abstract: Abstract. Scientific research in the 21st century has considerably improved our knowledge of soil organic matter and its dynamics, particularly under the pressure of the global disruption of the carbon cycle. This paper reviews the processes that control C dynamics in soil, the representation of these processes over time, and their dependence on variations in major biotic and abiotic factors. The most recent advances in soil organic matter knowledge are: – Most organic matter is composed of small molecules, de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 129 publications
1
15
0
Order By: Relevance
“…The necromass can be decomposed by enzymes in the soil matrix that are either present as exoenzymes or released by cell autolysis (Miltner et al, 2012;Schimel and Schaeffer, 2012). In addition, mechanical disruption of the residual cell envelopes by physical processes, e.g., shrinking and swelling of SOM as well as soil mixing due to bioturbation by macrofauna may also determine the fate (Bohlen et al, 2004;Basile-Doelsch et al, 2020). The ultimate fate of the necromass then depends on many factors: microbial decay, clay content, Fe or Al oxides, water content and pore system of the soil aggregates (Schimel et al, 2007).…”
Section: Turnover and Stabilization Of Microbial Necromass Turnover Of Microbial Biomassmentioning
confidence: 99%
“…The necromass can be decomposed by enzymes in the soil matrix that are either present as exoenzymes or released by cell autolysis (Miltner et al, 2012;Schimel and Schaeffer, 2012). In addition, mechanical disruption of the residual cell envelopes by physical processes, e.g., shrinking and swelling of SOM as well as soil mixing due to bioturbation by macrofauna may also determine the fate (Bohlen et al, 2004;Basile-Doelsch et al, 2020). The ultimate fate of the necromass then depends on many factors: microbial decay, clay content, Fe or Al oxides, water content and pore system of the soil aggregates (Schimel et al, 2007).…”
Section: Turnover and Stabilization Of Microbial Necromass Turnover Of Microbial Biomassmentioning
confidence: 99%
“…The processes regulating carbon retention and the formation (constraint 3) and decomposition of stabilized SOM (constraint 4) depend on interactions among the composition of carbon inputs, soil texture, and microbial communities. The protection of carbon as relatively simple organic products from microbial decomposition is associated with organomineral complexes (Basile-Doelsch et al, 2020;Lavallee et al, 2020). Management can disrupt these processes, but the complexities are not well-understood (Dignac et al, 2017).…”
Section: Retention and Stabilization Of Soil Carbonmentioning
confidence: 99%
“…As a result, the assumptions embodied in these models have become increasingly challenged in recent years. Various authors have argued that the idea of splitting SOM into distinct pools based only on chemical composition and degree of recalcitrance no longer corresponds to the latest picture available of the nature of SOM (Abramoff et al, 2018;Basile-Doelsch, Balesdent, & Pellerin, 2020;Blankinship et al, 2018;Dungait, Hopkins, Gregory, & Whitmore, 2012;Sainte-Marie et al, 2021;Yang, Zhang, Bourg, & Stone, 2021). Among the pieces of evidence that led to this perspective, Kleber et al (2011) showed that the oldest SOM contains a greater proportion of easily decomposable organic molecules, whereas the younger one contains organic structures that are supposed to be more stable, suggesting that "carbon age is not necessarily related to molecular structure or thermodynamic stability".…”
Section: Introductionmentioning
confidence: 99%